Comparative analysis of ascorbic acid content of three varieties of apple fruit sold in Lafia open markets, north central Nigeria - M. Akpomie, Timothy; U. Augustine, Abel; E. Anwani, Samuel; I. Aandaka, Benjamin (International Journal of Advanced Chemistry, 2021)
Ascorbic acid, also known as vitamin C, is a water-soluble vitamin which helps to boost the immune system, fight against infectious diseas-es, aids iron absorption and formation of collagen in humans and other animals. The ascorbic acid content of three varieties of apples (Red Delicious, Granny Smith and Golden Delicious apples) sold in Lafia, Nasarawa State, Nigeria was investigated using the iodometric titration method for comparative reasons. The results obtained showed the concentrations of the ascorbic acid in all three varieties of the fruit to be not only different but statistically so. The concentration of the analytes in order of increasing magnitude is; Golden Delicious (22.83mg/100g), Granny Smith (29.26 mg/100g) and Red Delicious (38.63 mg/100g). Though the differences in the respective concentration of the fruits were statistically significant (p <0.05), these observed differences may not just be a function of the fruit variety alone but also on other possible reasons attributable to the impact of temperature, growing season, storage, shipping conditions and even post-harvest number of days as well as the maturity of the respective apple variety at the time of harvest prior to analysis. Comparatively, the analysis indicated that the three apple varieties are varied in ascorbic acid content but are all good sources vital for healthy living.Â Â